SPEED OF SEISMIC WAVES TRAVELLING THROUGH THE EARTH CRUST WITHIN THE BALTIC SHIELD (ON THE BASIS OF THE REGIONAL SEISMIC RESEARCH DATA) - Vitrik, O.; Trypilskiy, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article considers peculiarities of velocity of seismic waves in the Earth's crust, according to regional seismic studies and the comparative analysis of high-speed characteristics of individual provinces of the Baltic Shield. For comparative data analysis, velocity of each province and average velocity data for individual provinces of the Baltic Shield in general and vertical velocity gradients data were used. Based on the interpretation data of crust, Lapland-Kola-Korel`ska and Svekofens`ka provinces revealed different velocity characteristics. This may indicate differences in material composition and stress state in the crust of the two provinces. The practical significance of the work is that this study is performed for the first time and the results can be used for comprehensive geological and geophysical model compilation of the crust of the Baltic Shield and geological data interpretation for regional seismic studies.
Keywords: Baltic Shield; the velocity of seismic waves; tectonic province; vertical velocity gradient; graph V = f(H)